Monitoring pork-free food products by Polymerase Chain Reaction (PCR) assay / Maimunah Mustakim, Prof Madya Dr Zainon Mohd Noor and Siti Nazrina Camalxaman - Mustakim, Maimunah; Mohd Noor, Zainon (Prof Madya Dr); Camalxaman, Siti Nazrina (2005)
Processed foods with Halal label (issued by Islamic Development of Malaysia, JAKIM) were selected randomly to be tested for pork-free authentication. As a reference subject, pork-derived processed foods and several types of raw meats were also tested. The investigation was performed by using PCR-RFLP technique, which detected polymorphisms of the conserved region in the mitochondrial cytochrome b (cyt b) gene segment. PCR-amplified 359 bp of cyt b gene using universal primers, CYTbl and CYTb2 from the food samples was further resolved by eight different types of restriction enzymes, Alul, Hindlll, BsaJl, Rsal, BstNl, Msel, Nsil and BstUl. Application of the PCR-RFLP techniques showed distinct DNA fragments in the individual food samples. However, only certain enzymes showed discrimination amongst the tested food samples.